VD_FINDINFO HC / 2024 / 163 vom 15. April 2024 - VD Tribunal cantonal (2024)
EXPULSION DE LOCATAIRE, CAS CLAIR, RÉSILIATION IMMÉDIATE, BAIL À LOYER, REJET DE LA DEMANDE | 257d CO, 87 al. 1 CO, 257 CPC (CH)